Using Evidence in Policies Addressing Rural NEETs: Common Patterns and Differences in Various EU Countries. Issue 2 (March 2022) - Petrescu, Claudia; Ellena, Adriano Mauro; Fernandes-Jesus, Maria; Marta, Elena
Using the policy narrative framework, this article examines the pathways through which the development of policies (related to rural/small towns young NEETs in various EU countries) are based on evidence. To do this, we consider the Youth Guarantee (YG), an EU program (2014–2020) developed in several member countries with the aim of socioprofessional inclusion of NEETs (young people aged 15–24 that are not in employment, education, or training). It examines how evidence is used for national policy-making and is taken into account by stakeholders. This study involves documentary analysis of YG in three European countries: namely, Romania, Italy, and Portugal. In addition, it involves 27 interviews with policy-makers and NGO leaders. The results show a predominantly statistical use of data exclusively managed by public institutions. Therefore, we emphasize the importance of consulting evidence from academia and NGOs to improve this policy.